THE INDICATOR OF QUALITY LIFE PATIENT WITH CHRONIC RENAL FAILURE BY HEMODIALYISIS BASED ON COPING STRATEGY - Evi Desnauli; Nursalam Nursalam; Ferry Efendi (Universitas Airlangga, 2017)
Introduction: Chronic kidney disease is a slow, progressive, and irreversible deterioration in renal function. Ultimately, it leads to end stage renal disesase which in this condition need for haemodialysis therapy to replace renal function. The coping of patient who undergo haemodialysis therapy is very important to promote the success of the therapy. The aim of this study was to find out the correlation between coping and quality of life in chronic haemodialysis patient. Method: This study was a cross sectional study. The sample were 13 patients with chronic kidney disease who undergo haemodialysis therapy. Samples were taken by purposive sampling. Independent variable was coping, and the dependent variable was quality of life. The data were collected using questionnaire and analyzed using chi square test or fisher exact test as alternative test from chi square test. Result: The result showed that most of respondents had adaptive coping and good quality of life. The result of fisher exact test showed that p = 0,038 (p < 0.05), it means that there was significant correlation between coping and quality of life of patient with chronic kidney disease who undergo haemodialysis therapy. Discussion: The conclusion of this research was coping could improve the quality of life of patient who undergo haemodialysis therapy. Further studies are recommended to extend this research using another design and sampling, and observe physical and laboratory examination for measuring quality of life to get better understanding.